Effect of Various Plasticizers in Different Concentrations on :Physical, Thermal, Mechanical, and Structural Properties of :Wheat Starch-Based Films - Mohammed, Abdulrahman A. B. A.; Hasan, Zaimah; Borhana Omran, Abdoulhdi A.; M. Elfaghi, Abdulhafid; Khattak, M.A.; Ilyas, R. A.; Sapuan, S. M. (Mdpi, 2023)
Biocomposite materials are essential for environmental protection, as they have the ability of substituting synthetic plastic with natural materials. This work investigated how different plas¬ticizers (Glycerol (G), Fructose (F), Sorbitol (S), and Urea (U)) affect the morphological, mechanical, thermal, and physical characteristics of films made of wheat starch at various concentrations (0%, 15%, 25%, and 35%). Plasticizers were added to improve the flexibility and homogeneity of the wheat starch-based bioplastic. Control film exhibited high tensile strength (38.7 MPa) with low elon¬gation (1.9%). However, films plasticized with 35% sorbitol showed the highest elongation, which was 60.7% at break. At 35% of all plasticizers, fructose showed the highest tensile strength, with 7.6 MPa. The addition of different plasticizers shows improvement in water resistance; films plasticized with glycerol had the lowest water absorption at 35% fructose (187.4%) and also showed coherent surfaces. Glycerol, sorbitol, and urea films showed a higher mass loss compared to fructose films. Fructose showed the highest performance after the analysis of the results, with low water absorp¬tion, water content, and mass loss and with high mechanical performance at 35% of fructose. SEM images show that the addition of fructose and glycerol improves the surface homogenate, while sorbitol and urea have a less compact structure with large pores.